EXPERIENCES OF REPERCUSSIONS FROM PARTICIPATION IN ONLINE DEBATE - Løvlie, Anders Sundnes; Ihlebæk, Karoline Andrea (AoIR Selected Papers of Internet Research, 2016)
Based on data from a survey among contributors (n=3470) to the online comments sections of four Norwegian newspapers, we investigate the following research question: How do contributors to online comments sections in newspaper websites describe their experiences of repercussions from participation in debates? Through analysis of two survey questions asking respondents whether they have experienced problems in everyday life after participating in online comments, we find that women to a larger degree report such problems. However, when studying the types of problems reported, we fail to replicate earlier findings about gender differences associated with different types of problems. Instead, we find a surprising dominance of relatively inconsequential issues, leading to a discussion about the communicative competencies of participants, and the challenge in facilitating online debate for people with limited knowledge and experience about what kind of repercussions to expect when posting controversial opinions in a public forum.